Logistics Concept of Management: A Systematic Approach to Dynamic Optimization of a Firm's Business Performance - Zekic, Zdravko; Samarzija, Luka (Prabandhan: Indian Journal of Management, 2013)
In today's turbulent times, in order to successfully solve the managerial problems faced while running a firm, the existing managing paradigms should be replaced with new ones. The mechanical, cause-and-consequence, linear and determinist understanding of today ought to be replaced with an organic, holistic and systematic approach focused on the synergetic processes of creating added value for all stakeholders of a given firm, which is perceived as a socio-economic system within the supra-system of its environment. Logistics, as a means of space and time transformation of goods, energy, information and knowledge, occurring through qualitative transformative processes of creating added value for all participants and oriented towards the optimal fulfillment of users' needs, becomes the infrastructure for managing the dynamic optimization of contemporary firm's operations. Namely, the holistic approach and activities founded on the flows of creating added value for users is the essence of the logistics conception of managing the firm's activities, i.e. the logistics concept of management. The logistics simulation models of dynamic optimization of business operations provide for a consistent system of managing variables, which are directed towards a processing harmonization of the firm's performance and the changes in the environment as an assumption of the optimal dynamic realization of the firm's success potential.